Relationship between species distribution of sandy alpine grasslands and microtopography in the source regions of Yangtze river - Zhao, Peng; Xu, Xianying; Tang, Jinnian; Jiang, Shengxiu (Frontiers in Environmental Science, 2022)
Sandy alpine grasslands are an important community type, it’s dynamic affect the progress and reversal of desertification in source regions of the Yangtse rivers. To understand geomorphic driving mechanism of species distribution pattern, we examined the species compositions and delineated the most important landform factors influencing species distribution of sandy alpine grassland using two-way indicator species analysis (TWINSPAN), detrended correspondence analysis (DCA), and canonical correspondence analysis (CCA). Field survey were conducted in summer of 2016 using stratified random methods in hilly sloped lands, floodplains, foothills, and valley land of study region. In total, 29 plant species grouped into 27 genera and 16 families were identified. L.chinensis, E.dahuricus and C.declinatum are the dominant species of sandy alpine grassland communities in different microtopography, which indicated that desertification of alpine grassland is in progress, and the vegetation community was successional to the direction of xeric. Standard frequency distribution varied with different microtopography, the proportion of dominant species was generally lower than that of rare species, and the vegetation community was in a highly successional stage. Seven groups were distinguished through TWINSPAN: AssI. L. secalinus+H.altaicus+S.woodiana, AssII. L.secalinus+K.royleana+C.declinatum, AssIII. L.secalinus+E. dahuricus+A.tenuifolia, AssIV. L.secalinus+T.alpine, AssV. E.sibiricus+P.annua, AssVI. E.sibiricus+E.dahuricus, AssVII. C. declinatum. The distribution of the seven associations in the DCA ordination graph showed species with similar ecotype is clustered together. The results of the CCA ordination reflected that slope and aspect are the dominant factors among microtopography determining the species distribution of sandy alpine grassland.